2014
DOI: 10.1149/06409.0147ecst
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Precursor Selection and the Thermal Atomic Layer Deposition of Copper/Manganese Alloy Films

Abstract: This paper describes the thermal ALD growth of Cu/Mn alloy films using the precursors Cu(OCHMeCH2NMe2)2, Mn2(tBuNCH-C(tBu)(Me)O)4, and BH3(NHMe2) at 160 °C. Deposition rates of about 0.09 Å/cycle were observed on a variety of substrates. Cu:Mn ratios of about 70:30 were obtained by controlling the number of Cu and Mn cycles. X-ray photoelectron spectroscopy confirms the presence of metallic Cu and Mn within the Cu/Mn alloys. Similar precursors and chemistry were used to deposit 35-50 nm thick Cu/Mn/Cu film sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Intermetallic phases in Pt–In, Pt–Sn, and Ni–Fe systems have been obtained by the postdeposition reduction of the corresponding ALD oxides. There are also some ALD studies on metal alloys, such as Pt–Ir, Pd–Pt, Ru–Pt, Ru–Co, Co–W, Co–Pt, Ru–Mn, and Cu–Mn, but no reports exist on materials exhibiting a specific intermetallic structure. Co–Sn and Ni–Sn with varying stoichiometry, including the intermetallic Co 3 Sn 2 and Ni 3 Sn 2 phases, have generally been prepared by, for example, ball milling, melting, different solution‐based techniques, solvo‐ and hydrothermal routes, electrodeposition, sputtering, and electron beam evaporation .…”
Section: Introductionmentioning
confidence: 99%
“…Intermetallic phases in Pt–In, Pt–Sn, and Ni–Fe systems have been obtained by the postdeposition reduction of the corresponding ALD oxides. There are also some ALD studies on metal alloys, such as Pt–Ir, Pd–Pt, Ru–Pt, Ru–Co, Co–W, Co–Pt, Ru–Mn, and Cu–Mn, but no reports exist on materials exhibiting a specific intermetallic structure. Co–Sn and Ni–Sn with varying stoichiometry, including the intermetallic Co 3 Sn 2 and Ni 3 Sn 2 phases, have generally been prepared by, for example, ball milling, melting, different solution‐based techniques, solvo‐ and hydrothermal routes, electrodeposition, sputtering, and electron beam evaporation .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] This chemistry does not extend to Ta metal and TaSix films are produced instead. 21,22 Subsequently, BH3(NHMe2) has been used to deposit Cu and other first row transition metal films [23][24][25] and has also been evaluated for Ag 26 and Au 27 metal ALD, but film growth in all cases is highly substrate dependent. Thus, there is a great need to develop new volatile reducing agents for ALD of these challenging elements and materials.…”
Section: Introductionmentioning
confidence: 99%
“…4,13 In the past few years, it has been well demonstrated that the atomic layer deposition (ALD) technique can guarantee depositions of various ultrathin films with excellent step coverage and accurate thickness controllability due to the self-limiting surface reaction mechanism. 1,15,16 Therefore, it is inferred that the ALD technology also might provide a great opportunity to prepare ultrathin Mn-based barrier films for interconnects of nanoscale integrated circuits. In this article, manganese oxynitride (i.e., MON for short) thin films are deposited by plasma-enhanced ALD (PE-ALD) using bis(ethylcyclopentadienyl)manganese (Mn(EtCp) 2 ) and NH 3 plasma as precursors.…”
Section: Introductionmentioning
confidence: 99%